Liquid-interface-assisted synthesis of covalent-organic and metal-organic two-dimensional crystalline polymers - Wang, Lihuan; Sahabudeen, Hafeesudeen; Zhang, Tao; Dong, Renhao (npj 2D Materials and Applications, 2018)
The development of synthetic two-dimensional crystalline polymers (2DCPs), such as 2D covalent-organic polymers and 2D metal-organic polymers, is receiving increasing attention due to their intriguing chemistry and unique properties, as well as potential role in wide ranging applications, such as electronics, sensing, catalysis, separation, and energy storage and conversion. Complementary to the top-down exfoliation towards the preparation of 2DCPs, bottom-up interface-assisted synthesis is advantageous in the 2D dynamic arrangement of the molecules or precursors, offering the chance to generate ultra-thin structures with large lateral sizes. This article provides guidelines on the preparation of free-standing, single-layer, or multi-layer 2DCPs via liquid-interface-assisted synthesis, mainly involving polymerization at the air–water and liquid–liquid interfaces, as well as the Langmuir-Blodgett method. Insight into the advantages and challenges of synthesis strategies and chemistry methodologies are provided for the future development of interfacial synthesis of 2DCPs with diverse structural and functional control.
CRIS-Team Scopus Importer:2022-04-14